2013
DOI: 10.1109/ted.2013.2258923
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Switching Printed Organic Electrochemical Transistors Including Electronic Vias Through Plastic and Paper Substrates

Abstract: Abstract-A novel vertical architecture for all-printed organic electrochemical transistors, based on PEDOT:PSS, realized on flexible substrates is reported. The transistors are manufactured along both faces of paper or plastic substrates and via connections are realized using laser ablation and simple punch through using a pin. Successful modulation of the electric current that flows between the two sides of the substrate is achieved using electrolyte-gating and electrochemical modulation of the electronic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Blaudeck et al demonstrated an OECT, with improved I on / I off ratio and reduced switching times, realized combining screen printing (source and drain contacts), inkjet‐printing (device channel) and laser ablation. Kawahara et al realized a vertical OECT structure both on plastic and on paper substrates. The device was composed of an inkjet‐printed PEDOT:PSS channel connected to an electrode deposited on the same side of the substrate and a via hole leading to the opposite side of the substrate, where the other electrode was deposited.…”
Section: Inkjet‐printing Of Organic Transistorsmentioning
confidence: 99%
“…Blaudeck et al demonstrated an OECT, with improved I on / I off ratio and reduced switching times, realized combining screen printing (source and drain contacts), inkjet‐printing (device channel) and laser ablation. Kawahara et al realized a vertical OECT structure both on plastic and on paper substrates. The device was composed of an inkjet‐printed PEDOT:PSS channel connected to an electrode deposited on the same side of the substrate and a via hole leading to the opposite side of the substrate, where the other electrode was deposited.…”
Section: Inkjet‐printing Of Organic Transistorsmentioning
confidence: 99%
“…A first attempt to make use of a vertical architecture in combination with poly(3,4‐ethylenedioxythiophene) doped with poly(styrenesulfonate) (PEDOT:PSS) deals with screen printed devices. Vertical vias in plastic or paper are exploited to make use of both sides of the substrate . Here, we demonstrate vertical organic electrochemical transistors (vOECTs) with PEDOT:PSS channels, fabricated using photolithography.…”
mentioning
confidence: 99%
“…The main challenge for the hybrid voltage equalizer is the long turn-ON time (up to seconds, depending on the humidity) of the OECTs, which limits its response speed to overcharging. The switching speed of the printed OECTs can be improved through materials and device structure [10,14]. The hybrid voltage equalizer, as a good example of hybrid electronics, paves a road towards low-cost fully-integrated energy storage systems with printed SCs.…”
Section: Discussionmentioning
confidence: 99%